Dampak Pengembangan Ekowisata Hutan Mangrove terhadap Sosial dan Ekonomi Masyarakat di Desa Kuala Langsa, Aceh - safuridar safuridar; Puti Andiny (Universitas Samudra, 2020)
The study aims to determine the social and economic impact on the development of Mangrove Forest Ecotourism in Langsa City. The analytical method used in this research is to identify the impact of mangrove forest development on the social and economic community in Langsa City. The sample amounted to 100 people who are affected by the community around the mangrove forest. Based on results, the development of mangrove forest ecotourism can increase community activities. Other impacts are opening new jobs, increasing income, increasing welfare, providing public facilities, increasing PAD, and others. While the lowest impact in the development of mangrove forests is the occurrence of social conflict in the community. The existence of mangrove forests greatly supports the level of social and economic development of the surrounding community. From an economic perspective, mangrove forests are a source of income from forest products that are of high economic value.